TRADISI INTELEKTUAL ISLAM DI INDONESIA ABAD VII-XXI M - Fabian Fadhly (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
The intellectual tradition of Islam evolved through three periods of classical times, medieval times and modern times. These three ages have different characteristics and methods of developing Islamic intellectual traditions, although the classical period has a strong influence on the development of Islamic intellectual traditions in later ages. This paper is put forward as an attempt to provide a proper understanding and meaning, how Islam is an integral part of the intellectual development of Muslims better known as Islamic intellectual traditions and is still going on today especially in Indonesia. Seeks to describe and demonstrate Islam has an important role in building an intellectual tradition that begins through teaching in cottages and / or boarding schools. The method put forward in this paper is descriptive method with analytical approach. The classical age contributes to the development of intellectuality by placing a growing method of teaching and education practiced from the time of Prophet Muhammad SAW methods of writing, writing and rote. The Middle Ages contributed to the emergence of institutions that helped and expanded the Islamic intellectual tradition. Modern era is a struggle of Indonesian Islamic intellectual tradition, which gave birth to two groups of young people and the elderly. Young people prioritize the importance of renewal of thought in the realm of Islamic understanding, with the method of restoring Islam in its place through the understanding of Islamic teachings that remove the taqlid side and purify the teachings of Islam Keywords: Islamic Intellectual Tradition Indonesia,